Digest: Biotic interactions shape local adaptation in teosinte populations. (14th October 2019) - Peede, David; Coughlan, Jenn
Abstract: Little is known about how microbial communities shape the expression of plant phenotypes and phenotypic correlations. This is precisely the question that O'Brien et al. addressed using populations of highland teosinte, a wild relative of maize. The authors find that both abiotic conditions and different rhizosphere compositions have a strong effect on teosinte phenotypes and correlations among traits. These results indicate that microbial communities might have a strong effect on plant trait expression.